Intersectoral and integrated approaches in achieving the right to health for refugees on resettlement: a scoping review. Issue 7 (1st July 2019) - Ho, Shirley; Javadi, Dena; Causevic, Sara; Langlois, Etienne V; Friberg, Peter; Tomson, Göran
Abstract : Background: Better understanding, documentation and evaluation of different refugee health interventions and their means of health system integration and intersectoral collaboration are needed. Objectives: Explore the barriers and facilitators to the integration of health services for refugees; the processes involved and the different stakeholders engaged in levaraging intersectoral approaches to protect refugees' right to health on resettlement. Design: Scoping review. Methods: A search of articles from 2000 onward was done in MEDLINE, Web of Science, Global Health and PsycINFO, Embase. Two frameworks were applied in our analysis, the 'framework for analysing integration of targeted health interventions in systems' and 'Health in All Policies' framework for country action. A comprehensive description of the methods is included in our published protocol. Results: 6117 papers were identified, only 18 studies met the inclusion criteria. Facilitators in implementation included: training for providers, colocation of services, transportation services to enhance access, clear role definitions and appropriate budget allocation and financing. Barriers included: lack of a participatory approach, insufficient resources for providers, absence of financing, unclear roles and insufficient coordination of interprofessional teams; low availability and use of data, and turf wars across governance stakeholders. Successful strategies to address refugee health included: networks of service delivery combining existing public and private services; system navigators; host community engagement to reduce stigma; translation services; legislative support and alternative models of care for women and children. Conclusion: Limited evidence was found overall. Further research on intersectoral approaches is needed. Key policy insights gained from barriers and facilitators reported in available studies include: improving coordination between existing programmes; supporting colocation of services; establishing formal system navigator roles that connect relevant programmes; establishing formal translation services to improve access and establishing training and resources for providers.